Clematis vitalba L.,Equisetum Ramosissium desf.,eryngium Maritimum L., Melissa officinalis L.subsp.altissima (Sm.) Arcangeli,typha domingensis pers.,üzerinde yapılan biyoaktivite tayinleri. - Sarıboyacı, Ümran (My University, 1994)
unknown
Keywords: TIP-FARMAKOGNOZİ